Functional abilities among young Croatian soccer players - Erceg, M.; Rada, A.; Sporis, G.; Antonic, D. (World Congress of Performance Analysis of Sport XII, 2018)
The main objective of this study was to determine functional abilities during treadmill protocol of young soccer players of different age categories. Sixty six players from the first Croatian soccer league for young players participated in this study. Players were divided into three age groups by 22 players (Pioneers U-15. Cadets U-17 and Juniors U-19). Maximum oxygen intake VO2max for U-15 age group was 4.1 l/min while the U-17 and U-19 had 4.22 l/min and 4.61 l/min respectively. Relative maximum oxygen intake RVO2max was also highest at the oldest group with 62.3 ml/min/kg what was higher then cadets (60.3 ml/min/kg) and pioneers (58.76 ml/min/kg. p<0.01). Maximum blood lactate concetration was measured with cadets 12.06 mmol/l what was just slightly higher then juniors (11.79 mmol/l). Both groups had statisticaly higher results when compared with pioneers (9.81 mmol/l. p<0.05). It is evident that functional abilities improve with age and training experiance.